A qualitative study on the social representations of populism and democracy in Peru - Espinosa, Agustin; Janos, Erika; Pacheco, Manuel; Cisneros, Renzo; Cueva, Fiorella; De Las Casas De La Lama, Renato; De La Cruz Bellido, Chrystian Noe; Grados, Camila; Huapaya, Carla; Mercado, Sebastián; Palacios, Danika; Reyes, Jackeline Elena; et al. (Frontiers in Political Science, 2024)
The purpose of this paper is to describe and analyze the social representations of democracy, populism and the relationship between both concepts in a sample of citizens from different regions of Peru (n = 76). To this end, a qualitative research design was proposed, using in-depth interviews, which were analyzed from a discursive approach. The results show that democracy and populism are two closely related concepts in tension. On the one hand, the social representation of democracy is semantically poor, closely related to electoral behavior and is seen as a political system that, ideally, is positively valued. Populism, on the other hand, is seen as a political strategy based on the manipulation of citizens' needs in order to reach power using the democratic process of elections. The representation of populism in general is negative, and it is mentioned that it appears and acquires strength in the face of citizen dissatisfaction with democracy, when it cannot solve problems of poverty, corruption or exclusion. The representations of populism take up the constitutive components proposed by different authors on the topic (people, elites and democracy as a product of popular will), but the participants do not necessarily structure the relationships between these components as proposed in the academic literature. Finally, the results shows that respondents' experiences with democracy and populism in Peru act as important socializing forces that will frame how citizens relate to politics and the public.